Bill Nye : science guy [videorecording (DVD)] - Fritch, William Ryan (PBS, 2018)
Bill Nye is a man on a mission, to stop the spread of anti-scientific thinking across the world. With intimate and exclusive access, as well as plenty of wonder and whimsy, this behind the scenes portrait of Nye follows him as he takes off his Science Guy lab coat and takes on those who deny climate change, evolution, and a science-based world view.